Penguatan Partisipasi Siswa Pada Kegiatan Jumat Pagi dalam Membentuk Kewarganegaraan Yang Baik di SMP Negeri 1 Teras - Hendrawan, Deviyanthi Putri; Muthali'in, Achmad (Jurnal Kewarganegaraan, 2023)
AbstractThe focus of the research is on increasing student participation in Friday morning activities as a means of fostering good citizenship. Participation contributes to activities carried out conscientiously and responsibly; therefore, schools become a vehicle for building the younger generation, particularly in Pancasila and Citizenship Education, which relate to behavior, norms, perspectives, and national values. The focus of the research was on the notion that the Friday morning habituation program increased student participation, which could shape students into good citizens. This study seeks to determine the effect of increased student participation in Friday morning activities on the development of good citizenship. This study employs descriptive qualitative and flow model analysis methodologies. The results of the study indicate that Friday Morning activities can strengthen student participation in developing good citizenship, as indicated by five indicators of participation-strengthening abilities. Several students did not participate and the weather constituted the obstacles. The solutions provided are in the form of scores and motivational, regardless of the weather, students can adopt other indoor-active habits. The conclusion is that student participation in Friday Morning activities at SMP Negeri 1 Teras strengthens the formation of good citizenship.---------------AbstrakFokus penelitian adalah penguatan partisipasi siswa pada kegiatan jumat pagi dalam membentuk kewarganegaraan yang baik. Partisipasi merupakan kontribusi kegiatan yang dilakukan secara sadar dan bertanggung jawab, maka sekolah menjadi wadah dalam membangun generasi muda terutama pada Pendidikan Pancasila dan Kewarganegaraan karena berhubungan dengan tingkah laku, norma, pandangan serta nilai kebangsaan. Fokus penelitian melihat adanya penguatan partisipasi siswa setelah diadakannya program pembiasaan jumat pagi yang dapat membentuk siswa memiliki kewarganegaraan yang baik. Penelitian ini bertujuan mengetahui penguatan partisipasi siswa pada kegiatan jumat pagi dalam membentuk kewarganegaraan yang baik. Penelitian menggunakan kualitatif deskriptif dengan teknik analisis model alir. Hasil penelitian bahwa kegiatan Jumat Pagi mampu menguatkan partisipasi siswa dalam membentuk kewarganegaraan yang baik, ditunjukkan dari lima indikator penguatan kemampuan partisipasi. Kendalanya beberapa siswa yang tidak berpartisipasi dan cuaca. Solusi yang diberikan berupa skor dan dorongan motivasi, sedangkan cuaca dapat dialihkan pembiasaan lain yang beraktivitas dalam ruangan. Kesimpulan terdapat penguatan partisipasi siswa melalui kegiatan Jumat Pagi dalam membentuk kewarganegaraan yang baik di SMP Negeri 1 Teras.